A randomized double-blind multi-center trial of hydrogen water for Parkinson's disease: protocol and baseline characteristics. Issue 1 (December 2016) - Yoritaka, Asako; Abe, Takashi; Ohtsuka, Chigumi; Maeda, Tetsuya; Hirayama, Masaaki; Watanabe, Hirohisa; Saiki, Hidemoto; Oyama, Genko; Fukae, Jiro; Shimo, Yasushi; Hatano, Taku; Kawajiri, Sumihiro; et al.
Abstract Background Our previous randomized double-blind study showed that drinking hydrogen (H2 ) water for 48 weeks significantly improved the total Unified Parkinson's Disease Rating Scale (UPDRS) score of Parkinson's disease (PD) patients treated with levodopa. We aim to confirm this result using a randomized double-blind placebo-controlled multi-center trial. Methods Changes in the total UPDRS scores from baseline to the 8th, 24th, 48th, and 72nd weeks, and after the 8th week, will be evaluated. The primary endpoint of the efficacy of this treatment in PD is the change in the total UPDRS score from baseline to the 72nd week. The changes in UPDRS part II, UPDRS part III, each UPDRS score, PD Questionnaire-39 (PDQ-39), and the modified Hoehn and Yahr stage at these same time-points, as well as the duration until the protocol is finished because additional levodopa is required or until the disease progresses, will also be analyzed. Adverse events and screening laboratory studies will also be examined. Participants in the hydrogen water group will drink 1000 mL/day of H2 water, and those in the placebo water group will drink normal water. One-hundred-and-seventy-eight participants with PD (89 women, 89 men; mean age: 64.2 [SD 9.2] years, total UPDRS: 23.7 [11.8], with levodopa medication: 154 participants, without levodopa medication: 24 participants; daily levodopa dose: 344.1 [202.8] mg, total levodopa equivalent dose: 592.0 [317.6] mg) were enrolled in 14 hospitals and were randomized. Discussion This study will confirm whether H2 water can improve PD symptoms. Trial registration UMIN000010014 (February, 13, 2013)